Foundations of bioethics - Gómez-Lobo, Alfonso (Acta Bioethica, 2009)
After pointing out that Bioethics is just applied ethics, the article describes three bioethics fundamentals: utilitarianism, of principles and the basic good, examining their main postulates and revealing their apparent limitations. The article concludes that it is not possible to do bioethics in a reflexive form without a critical knowledge of options in moral philosophy and in ontology, and from which the main current disagreement with the application of ethics to the domain of human life are derived.